STRATEGI KESANTUNAN BERBAHASA DALAM TINDAK TUTUR SANTRI PEREMPUAN PONDOK PESANTREN AL-MASRURIYYAH TEBUIRENG JOMBANG - Olivia Andi Calista; Mulyono; Dianita Indrawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the linguistic politeness in the speech acts of female students (santri) at Al-Masruriyyah Islamic Boarding School, Tebuireng, Jombang. The research focuses on politeness strategies, politeness maxims, and forms of polite expressions used by the santri during teaching and learning activities, particularly in Bandongan classes, Madrasah Diniyyah, and the Takhasus Program. A qualitative approach with a descriptive method was employed. Data were collected through non-participant observation, listening, recording, and note-taking techniques, and analyzed using politeness theories by Brown and Levinson (1987) & Leech (1983). The findings reveal that the santri apply various politeness strategies such as positive politeness, negative politeness, and off-record strategies. These findings affirm that the santri’s communicative practices in the pesantren environment reflect not only religious values but also pragmatic awareness in maintaining social harmony through language. Keywords: linguistic politeness, speech act, pragmatics, pesantren